2016
DOI: 10.4103/0019-5413.177581
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of one-stage combined osteotomy in Legg-Calve’-Perthes disease

Abstract: Background:Legg-Calve´-Perthes disease (LCPD) is an idiopathic avascular necrosis of the femoral head. There are multiple approaches to the treatment of LCPD ranging from conservative management to a wide variety of surgical methods. Conservative management necessitates extreme degrees of abduction in an orthosis for a longer period of time which further jeopardize capital femoral head vascularity. Surgical containment methods are used in cases where it is desirable. Initial surgical containment methods are va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
1
0
3
Order By: Relevance
“…At the same time, the pressure within the acetabulum remains normal which is vital to decrease the potential risk for AVN. Since then, several studies ( 14 , 17 21 ) reported the effect of the combined surgery. Vukasinovic et al ( 21 ) recommended that the combined surgery is valuable for the treatment of more severe cases of LCPD, especially for patients with older age ( 22 ), thus preventing the establishment of early secondary hip arthrosis.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the pressure within the acetabulum remains normal which is vital to decrease the potential risk for AVN. Since then, several studies ( 14 , 17 21 ) reported the effect of the combined surgery. Vukasinovic et al ( 21 ) recommended that the combined surgery is valuable for the treatment of more severe cases of LCPD, especially for patients with older age ( 22 ), thus preventing the establishment of early secondary hip arthrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Самую большую группу операций составляют различные ацетабулопластики, дополненные при необходимости межвертельной остеотомией [42][43][44][45]. В большинстве случаев ортопеды предпочитают использовать остеотомии таза по Солтеру и модификации тройной остеотомии таза типа Steel, Tonnis, chiari, ротационной ацетабулярной остеотомии, Ganz, Bernese [43]. Эта группа оперативных вмешательств имеет ряд преимуществ: выведение очага некроза из-под нагрузки с надежной фиксацией костных фрагментов и восстановление биомеханически выгодных взаимоотношений суставных концов.…”
unclassified
“…Эта группа оперативных вмешательств имеет ряд преимуществ: выведение очага некроза из-под нагрузки с надежной фиксацией костных фрагментов и восстановление биомеханически выгодных взаимоотношений суставных концов. Кроме того, сроки послеоперационной реабилитации значительно сокращаются [42,43]. Также данные операции явля ются методом выбора лечения БЛКП тяжелых стадий [43].…”
unclassified
See 1 more Smart Citation